Lebanon Economic Monitor, Spring 2014 : A Sluggish Economy in a Highly Volatile Environment - World Bank (Washington, DC, 2015)
Lebanon faces serious challenges from a volatile security environment and spillovers from the ongoing Syrian conflict which pose serious risks to an already fragile internal political situation. Security incidents have become increasingly more common and the volatile security environment is weakening consumer and investor sentiments and adversely affecting tourism, a central contributor to economic growth and employment in Lebanon. The influx of Syrian refugees to Lebanon persists, with officially registered refugees reaching close to 1 million (i.e., 21.6 percent of Lebanon’s pre-conflict population), which poses significant fiscal, health and educational challenges.